2019
DOI: 10.4025/actascitechnol.v41i1.38038
|View full text |Cite
|
Sign up to set email alerts
|

Geomechanical properties of mixtures of iron ore tailings improved with Portland cement

Abstract: This study aimed to use iron ore tailings in the construction of road pavements and embankments. To this end, it was investigated the geomechanical properties of mixtures of two iron ore tailings, improved with cement, whose results are important to characterize the behavior of mixtures regarding the mechanical actions imposed to the structural layer of paved roads. The results indicated that the studied tailings and mixtures without addition of cement presented uniform particle size, and despite having a CBR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The mixtures belonging to classes I, II, and III were developed with the same purpose: to apply the tailings in structural layers of pavements, such as base layers, sub-base, and subgrade reinforcement (ANTT, 2018;DANTAS, 2015;GALHARDO, 2015;BASTOS, 2013;CAMPANHA, 2011;PEIXOTO, 2006;BARATI et al, 2020;OLIVEIRA et al, 2019;OJURI et al, 2017;GRASSE et al, 2019;SÁ et al, 2019).…”
Section: Class I Ii and Iii Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixtures belonging to classes I, II, and III were developed with the same purpose: to apply the tailings in structural layers of pavements, such as base layers, sub-base, and subgrade reinforcement (ANTT, 2018;DANTAS, 2015;GALHARDO, 2015;BASTOS, 2013;CAMPANHA, 2011;PEIXOTO, 2006;BARATI et al, 2020;OLIVEIRA et al, 2019;OJURI et al, 2017;GRASSE et al, 2019;SÁ et al, 2019).…”
Section: Class I Ii and Iii Mixturesmentioning
confidence: 99%
“…Analyzing the compressive strength of soil cement (BASTOS, 2013;BARATI et al, 2020;OLIVEIRA et al, 2019;SÁ et al, 2019), the mixtures with 5% of cement showed lower strengths than those recommended by the DNIT (2005) for minimum strength at 7 days which must be between 1.4 and 2.1 MPa so that the mixture can be used as a sub-base layer and above 2.1 MPa to be used as a base layer. The mixtures with 10% and 15% of cement were shown to be suitable for use as a base layer for pavements.…”
Section: Class I Ii and Iii Mixturesmentioning
confidence: 99%
“…Stabilisation, which may regulate the shrink-swell characteristics of a soil and/or increase its strength, increases a subgrade's ability to support pavements and bear more weight. [1][2][3][4][5][6][7][8]. Black cotton soils are weak soils that are the most problematic from a technical standpoint because they may expand or contract.…”
Section: Introductionmentioning
confidence: 99%